Recommendations for rehabilitation and corrosion protection of a 100-year-old steel bridge (Durgadee) across heavily polluted river near Mumbai, India - Bhonge, Sanjay; Dalwi, Pradeep; Kulkarni, Jayant; Manjrekar, Surendra (Revista ALCONPAT, 2020)
This paper describes the rehabilitation proposal, methodology of evaluation of distress and likely remedial measures for 100 years old steel bridge on Ulhas river, near Mumbai. The bridge is constructed in year 1914 during British era apparently now heritage bridge as it was constructed with unique structural arrangement of jack arch decking and warren truss girder with verticals. After structural audit in 2000, it revealed the deterioration of steel parts and concrete initiated long back because of humid atmosphere and pollution in the area. Durgadee bridge showed various signs of bridge distress like major cracks in masonry abutments, heavy corrosion of Mild Steel (MS) structural members, non -functioning of expansion joints and bearings, failure of jack arch roof plates, de-bonding of concrete and exposed reinforcement etc. Paper discusses recommendations for rehabilitation and corrosion protection.